Suatu Kajian Tentang Bilangan Sempurna - Saiful Amri; Mahmudi Mahmudi (Department of Statistics, Syiah Kuala University, 2019)
Dalam tulisan ini akan dijelaskan mengenai kriteria bilangan sempurna genap dan bentuk bilangan sempurna ganjil (jika ada). Jika 2^k-1 prima maka 2^k-1(2^k-1) berupa bilangan sempurna. Sebaliknya, semua bilangan sempurna genap berbentuk 2^k-1(2^k-1) , dimana 2^k-1 prima. Maka masalah menentukan bilangan sempurna genap setara dengan menentukan k sehingga 2^k-1 prima. Bilangan 2^k-1 disebut sebagai bilangan Mersenne dan ditulis dengan M_k. In this paper will be explained about the criteria of the even perfect numbers and the form of odd perfect numbers (if any). If is prime, then is perfect. Conversely, all even perfect numbers are of the form with is a prime. Thus, finding even perfect numbers is equivalent to find the integers for which is prime. The numbers of the form called Mersenne numbers and is denoted by .